Determination of rational number of heat recovery units for the barn for 400 heads  - V. F. Khlystunov; S. V. Braginets; A. N. Tokareva; A. Y. Popenko (Advanced Engineering Research)
Introduction. Matters of selection and use of units for exhausted air heat utilization in the barn room are considered. The work objective is rationale for choosing the number of heat recovery devices that provide the greatest economic benefit when operating in the room for 400 animals.Materials and Methods. Determination of the number of energy-saving equipment units is due to several factors. The key one is the ever varying amount of air exchange in the barn depending on the outer air parameters. At this, the operating conditions in the southern regions of the country are taken into account. Mathematical models describing dependence of the technical-and-economic indices on the number and operating period of the disposal plants are proposed. The correlationregression analysis of the dependences obtained is made. The technical-and-economic assessment of the use of heat exchangers is carried out on its basis. Contour plots of the objective functions of the electric power consumption and operating costs are presented depending on the operating period and the capacity of energy-saving plants. A comparison method is used to identify the most efficient performance of the heat exchanger with the varying value of air exchange.Research Results. The desired number of heat exchangers, which provide the required air exchange in the livestock house, is determined. New mathematical models are developed for calculating the efficiency of utilization facilities taking into account the capacity and operating period. Dependences of the change in running costs on the performance efficiency of the utilizers are established. The number and type of the heat recovery units is determined. When these utilizers are in use, the greatest net present value is achieved.Discussion and Conclusions. The results obtained can be used to develop energy-saving systems under stock-rearing. The proposed mathematical models for calculating operational costs allow for a pre-feasibility study on the use of plate heat exchanger in livestock buildings.